Adaptability and nutritional analysis of a newly isolated Chlorella sp. NeZha in brackish and marine environments with potential bioeconomic impacts - Yuan, Shuai; Du, Ming; Li, Xianhui; Xu, Ke; Zhang, Kaining; Liu, Xiaoya; Wang, Jiangxin (Frontiers in Nutrition, 2024)
The microalga Chlorella sp. NeZha, recently isolated from a balcony environment, demonstrates remarkable adaptability across diverse salinity conditions, including seawater (SeaW), freshwater (FreshW), and elevated salinity levels (45‰). This study characterizes its morphological and genetic properties, confirming its taxonomy via optical microscopy and DNA sequencing. Cultivation in a 400 L outdoor photobioreactor revealed that Chlorella sp.NeZha produces chlorophyll a at concentrations surpassing those of seaweed and Spirulina by tenfold and fivefold, respectively, with a dry weight chlorophyll a content of 34.25 mg/g and 25 pg/cell. The microalga also contains substantial levels of carbohydrate (~33%), protein (~20 %) and lipids (~14 %). The microalga Chlorella sp. Nezha exhibits compatibility with various zooplankton species, such as rotifers and brine shrimp, which actively ingest it.Additionally, Chlorella sp. NeZha exhibits promising growth in aquaculture wastewater, suggesting its potential utility in bioremediation. These findings position Chlorella sp. NeZha as a viable candidate for sustainable aquaculture practices and biotechnological applications due to its high nutritional value and environmental resilience.